Thermally exfoliated π–π stacked blistered graphene oxide as efficient flame retardant soft nano-bundles for vinyl ester resin composites. Issue 1 (24th December 2020) - Cheedarala, Ravi Kumar; Song, Jung Il
Abstract : In this article, we synthesized thermally exfoliated blistered graphene oxide (BGO) soft nano bundles from graphene oxide (GO) by a thermal heating method. Abstract : In this article, we synthesized thermally exfoliated blistered graphene oxide (BGO) soft nano bundles from graphene oxide (GO) by a thermal heating method. GO was prepared using the noted Hummers' method from graphite flakes. BGO soft nano bundles can be used as an efficient flame retardant nanofiller in vinyl ester resin. The flame retardancies are progressively enhanced by delayed periods using 0.1 wt% and 1 wt% of BGO–VE. The heat release rates (HRR) were improved after doping of BGO in VER, respectively, in comparison to the pristine vinyl ester (VE) composite. These results demonstrated the noteworthy development in the fireproofing performance of the VE composites. The burning time and burning rates of the BGO–VE composites from the VE composite were increased from 6.28 min to 11.2 min and decreased from 11.93 min to 6.7 min, respectively. 1 wt% of BGO in VER is an ideal case for enhancing the flame retardancy tests. The robust flame retardancy and thermal performance of BGO–VER indicate promising scientific advances in emerging novel flame retardancy material.